Efektivitas Ekstrak Daun Serai (Cymbopogon citratus) terhadap Pertumbuhan Prevotella intermedia pada Basis Akrilik Piranti Ortodonti Lepasan - Desi Watri; Davin Davin; Dalilah Fadia Putri (LPPM Institut Pendidikan Nusantara Global, 2026)
This laboratory experimental study aimed to evaluate the effectiveness of lemongrass (Cymbopogon citratus) leaf extract against the growth of Prevotella intermedia on the acrylic base of removable orthodontic appliances. Acrylic samples measuring 10 × 10 × 2 mm were contaminated with Prevotella intermedia ATCC 25611, then treated with lemongrass extract at concentrations of 40% and 50%, 0.2% chlorhexidine gluconate as the positive control, and DMSO as the negative control. The number of bacterial colonies was subsequently counted using the total plate count method. The Kruskal–Wallis test showed significant differences among the groups (p = 0.000). The 50% extract produced a greater reduction in colony numbers than the 40% extract, although both remained less effective than chlorhexidine. The Mann–Whitney analysis also demonstrated significant differences across all treatment pairs (p = 0.004). These findings indicate that lemongrass leaf extract exhibits antibacterial activity against Prevotella intermedia but requires higher concentrations to achieve optimal effectiveness comparable to synthetic agents. Thus, lemongrass extract has potential as a natural adjunct to help reduce bacterial colonization on the acrylic base of removable orthodontic appliances.